BMI growth trajectory from ages 2 to 6 years and its association with maternal obesity, diabetes during pregnancy, gestational weight gain, and breastfeeding. Issue 2 (5th November 2019) - Wang, Xinhui; Martinez, Mayra P.; Chow, Ting; Xiang, Anny H.
Summary: Objective: To identify latent BMI growth trajectories from ages 2 to 6 years and examine their independent associations with maternal prepregnancy obesity or overweight, pre‐existing type 1 (T1D) or type 2 diabetes (T2D) or gestational diabetes (GDM) with or without requiring antidiabetic medications during pregnancy, excessive gestational weight gain (EGWG), and breastfeeding ≤ 6 months. Research design and method: Data included 71 892 children born at Kaiser Permanente Southern California hospitals in 2007 to 2011 with complete information on maternal risk factors. Group‐based trajectory modelling was used to identify latent BMI trajectory groups. Logistic regression was used to assess independent associations adjusted for covariates. Results: Three distinct BMI trajectory groups were identified: Group 1 (59% of the cohort) had stable low BMI, Group 2 (35% of the cohort) had stable median BMI, and Group 3 (6% of the cohort) had high and increasing BMI over time. Relative to Groups 1 and 2 combined, the adjusted odds ratio (OR) (95% CI) of being in Group 3 associated with maternal exposures were 5.6 (5.1‐6.2) for prepregnancy obesity, 2.4 (2.2‐2.7) for prepregnancy overweight, 2.1 (1.2‐3.7) for T1D, 1.6 (1.4‐1.8) for T2D, 1.4 (1.3‐1.6) for GDM requiring medication treatment, 1.1 (1.0‐1.3) for GDM not requiring medication, 1.3 (1.2‐1.4) for EGWG, and 1.2 (1.2‐1.3) for breastfeeding ≤ 6 months. Conclusion: Child's high and increasing BMI trajectory was strongly associated with maternal prepregnancy obesity and overweight, modestly associated with maternal T1D, T2D, and GDM requiring medication treatment and EGWG, and slightly associated with breastfeeding ≤ 6 months. GDM not requiring medication treatment during pregnancy had little association.